The structure of Second Corinthians: Paul's theology of ministry - Hiramatsu, Kei (Library of New Testament studies, 2023)
"Employing an inductive approach, this volume proposes that Paul's second letter to the Corinthians consists of seven major segments which coherently develop Paul's discourse pertaining to ministry"--